PERSONAL HYGIENE MANDI DALAM PENCEGAHAN DEKUBITUS PASIEN STROKE - Moh Alimansur; Hengky Irawan (Jurnal Penelitian, 2020)
Stroke patients are often treated with prolonged bed rest. This condition makes stroke patients vulnerable to pressure sores. Maintaining the patient's hygiene by bathing the patient can be an effort to reduce the risk of pressure sores. The purpose of this study was to determine the effect of personal hygiene bathing with the incidence of pressure sores. The research design used was descriptive-analytic. The study population was all stroke patients who were hospitalized in the Kediri City Regional Hospital. Sampling technique with Purposive Sampling. The sample size obtained was 40 respondents. Data was collected using observation and interview sheets. Data analysis uses ordinal regression analysis. The results of the ordinal regression analysis obtained a p-value of 0,000 which means that bathing the patient will reduce the number of pressure sores in stroke patients. Bathing the patient will increase patient comfort, patient satisfaction, smooth blood flow, and certain tissue pressures can be reduced so that the risk of damage to skin tissue or pressure sores can be prevented. The recommendation that can be given is to bathe the patient must be done routinely and correctly according to the patient's condition.